PENGARUH VARIASI PENGGUNAAN NACA 0018 SEBAGAI FIN PADA KEMUDI DENGAN TIPE NACA 0010 TERHADAP EFISIENSI PROPELLER - Rizky Rasyid Wibawanto (2023)
In an era of rapidly advancing technology, awareness of the importance of efficient energy use is also increasing. In the maritime world, there is a term known as Energy Saving Device (ESD) used on ships to save fuel consumption. Based on Huang et al.'s research, it has been proven that a rudder with an additional fin can generate additional thrust force. The purpose of this study is to find the most optimal propeller efficiency based on variations in fin position and fin angle. The initial step involves modeling the propeller, rudder, and fin. The study is conducted using Computational Fluid Dynamics (CFD) software, specifically Ansys Fluent. According to the research, the most optimal propeller efficiency is achieved when the fin is positioned in the middle and has a 6-degree angle. This configuration results in a 0.6230% increase in propeller efficiency.